601 Association of sleep deprivation and the risk of developing systemic lupus erythematosus among women. (14th December 2022) - Choi, May Y; Malspeis, Susan; Sparks, Jeffrey A; Cui, Jing; Yoshida, Kazuki; Costenbader, Karen H
Abstract : Objective: Sleep deprivation has been associated with risk of autoimmune diseases. We investigated whether it was associated with risk of developing SLE using the Nurses' Health Study (NHS) (1986-2016) and NHSII (1989-2017) cohorts. Methods: Average sleep duration in a 24-hour period was reported in the NHS (1986-2014) and in NHSII in (1989-2009). Lifestyle, exposure and medical information was collected on biennial questionnaires. Adjusted Cox regression analyses modeled associations between cumulative average sleep duration (categorical variables) and incident SLE (figure 1). Interactions between sleep duration and shiftwork, bodily pain (Short-Form 36 questionnaire) and depression were examined. Results: We included 186, 072 women with 187 incident SLE cases during 4, 246, 094 person- years of follow-up (table 1). Chronic low sleep duration (≤5 hours/night vs reference >7-8 hours) was associated with increased SLE risk (adjusted HR 2.47, 95%CI:1.29-4.75) (table 2), which persisted after the analysis was lagged (4 years, adjusted HR 3.14, 95%CI1.57-6.29) and adjustment for shiftwork, bodily pain, and depression (adjusted HR 2.13, 95%CI:1.11-4.10) (table 3). We detected additive interactions between low sleep duration and high bodily pain (SF-36 <75) with an attributable proportion (AP) of 64% (95%CI:40%-87%) and HR for SLE of 2.97 (95%CI:1.86-4.75) for those with both risk factors compared to those with neither. Similarly, there was an interaction between low sleep duration and depression with an AP of 68% (95%CI:49%-88%) and an HR for SLE of 2.82 (95%CI:1.64-4.85). Conclusion: Chronic low sleep duration was associated with higher SLE risk, with stronger effects among those with bodily pain and depression, highlighting the potential role of adequate sleep in disease prevention.